Association of Baseline Patient-reported Health-related Quality of Life Metrics with Outcome in Localised Prostate Cancer. Issue 1 (January 2022) - Roy, S.; Morgan, S.C.; Spratt, D.E.; MacRae, R.M.; Grimes, S.; Malone, J.; Mukherjee, D.; Malone, S.
Abstract: Aims: Although health-related quality of life (HR-QoL) outcomes are pivotal in oncology, the prognostic significance of patient-reported HR-QoL metrics is largely undefined in localised prostate cancer. We report the association of baseline HR-QoL metrics with overall survival and toxicity in localised prostate cancer. Materials and methods: This was a secondary analysis of a phase III randomised controlled study conducted in a single-payer health system. Patients with Gleason score ≤7, clinical stage T1b–T3a and prostate-specific antigen <30 ng/ml were randomised to neoadjuvant and concurrent androgen deprivation therapy (ADT) for 6 months starting 4 months before prostate radiotherapy or concurrent and adjuvant ADT for 6 months starting simultaneously with prostate radiotherapy. HR-QoL scores were estimated using the European Organisation for Research and Treatment of Cancer QoL questionnaire. A multistate Markov model was used to determine the association of baseline HR-QoL metrics with overall survival and a multilevel multivariable Cox regression was used to determine the association with the incidence of delayed-onset grade ≥3 radiotherapy-related toxicities. To adjust for multiple analyses, P < 0.025 was considered as statistically significant. Results: Overall, 393 patients with baseline HR-QoL data were included in this analysis: 194 in the neoadjuvant arm and 199 in the adjuvant arm. Baseline financial difficulty (hazard ratio 1.020, 95% confidence interval 1.010–1.030, P = 0.02) and dyspnoea (hazard ratio 1.020, 95% confidence interval 1.003–1.030, P = 0.01) were associated with inferior overall survival. Baseline dyspnoea was associated with a higher incidence of grade ≥3 toxicity (hazard ratio 1.020, 95% confidence interval 1.010–1.030, P = 0.023). Conclusion: In a cohort of localised prostate cancer patients treated with radiotherapy and short-term ADT, a 10-point higher baseline financial difficulty or dyspnoea was associated with a 20% increased risk of death. With each 10-point increase in baseline dyspnoea, we noted a 20% increase in the associated risk of grade ≥3 delayed-onset radiotherapy-related toxicity. Highlights: A 10-point higher baseline financial difficulty portended a 20% increased risk of death. A 10-point higher baseline dyspnoea portended a 20% increased risk of death. A 10-point increase in dyspnoea, was associated with 20% increase in the risk of grade ≥3 late toxicity.